2018
DOI: 10.3390/ijms19051284
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation with Oleum Cinnamomi Improves Intestinal Functions in Piglets

Abstract: The present study was to determine the efficacy of dietary supplementation with oleum cinnamomi (OCM) on growth performance and intestinal functions in piglets. Sixteen piglets (24-day-old) were randomly assigned to the control or OCM groups. Piglets in the control group were fed a basal diet, whereas piglets in the OCM group were fed the basal diet supplemented with 50 mg/kg OCM. On day 20 of the trial, blood samples and intestinal tissues were obtained from piglets. Compared with the control group, dietary O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 41 publications
(59 reference statements)
0
16
0
Order By: Relevance
“…The primer pairs (Table 1) used to amplify cDNA fragments were used for qPCR as previously described by Yi et al (34). with continuous fluorescence measurement and final cooling to room temperature was processed.…”
Section: Qpcr Analyses For Gene Expression In Intestinementioning
confidence: 99%
“…The primer pairs (Table 1) used to amplify cDNA fragments were used for qPCR as previously described by Yi et al (34). with continuous fluorescence measurement and final cooling to room temperature was processed.…”
Section: Qpcr Analyses For Gene Expression In Intestinementioning
confidence: 99%
“…Among these substitutes, plant feed additives are promising but diverse additives that promote the health and performance of poultry ( Windisch et al, 2008 ; Hashemi and Davoodi, 2010 ). Feed palatability and high ileum digestibility of feed are considered the main mechanisms of the growth-promoting effects of plant-derived feed additives, most of which increase the secretion of islet enzymes ( Yi et al, 2018 ). In recent studies, effects of these additives on intestinal microbiota indicate their beneficial effect on performance ( Zhai et al, 2018 ), antioxidative protection systems ( Chowdhury et al, 2018 ), the immune system ( Yang et al, 2018 ), and anti-inflammatory responses of animals ( Griss et al, 2018 ; Liu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although our results showed that dietary supplementation with E. faecium R1 can significantly improve the growth performance of weaned piglets, the underlying mechanism is still unknown. The changes in blood biochemical indexes in pigs are a reflection of changes in cell permeability and metabolic function of animals [ 43 ]. Some studies have shown that increased activity of alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP) in the blood is usually a marker of the stress response and also indicates liver damage [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%